Muscle density discriminates hip fracture better than computed tomography X‐ray absorptiometry hip areal bone mineral density. Issue 6 (7th September 2020) - Wang, Ling; Yin, Lu; Zhao, Yue; Su, Yongbin; Sun, Wei; Liu, Yandong; Yang, Minghui; Yu, Aihong; Blake, Glen Mervyn; Cheng, Xiaoguang; Wu, Xinbao; Veldhuis, Annegreet; et al.
Abstract: Background: Muscle weakness is a key factor in the increase risk of falls and might also play a significant role in the increase of risk of hip fracture. Computed tomography‐measured muscle size and muscle density are well‐established imaging biomarkers used in studies of physical function, frailty or cancer, but limited to hip fracture. In particular, it is warranted to have a better understanding of the performance of muscle size and density in the discrimination of acute hip fractures. We also aim to determine age‐related differences of muscle size and density in healthy controls and hip fracture patients. Methods: Four hundred thirty‐eight low‐energy acute hip fracture cases and 316 healthy controls from the China Action on Spine and Hip Status study were included in the study. Muscle cross‐sectional area and density were measured for the gluteus maximus and gluteus medius and minimus. Areal bone mineral density (aBMD) of the femoral neck and total hip was measured. Using propensity score matching, we generated three samples with cases and controls matched for age, body mass index, and gender: femoral neck fracture (FNF), intertrochanteric fracture (ITF), and any hip fracture vs. controls, respectively. Results: Handgrip strength, gluteus muscle area and density, and bone parameters of the matched hip fracture groups were lower than those of the correspondence control groups, respectively ( P < 0.05). The univariate analysis showed that associations of aBMD with FNF and with ITF were significantly weaker than associations between fracture and muscle parameters. Gluteus medius and minimus muscle density showed the highest areas under the curve (AUC) with FNF (0.88, 95% confidence interval, 0.85–0.92) and trochanteric fracture (0.95, 95% confidence interval, 0.92–0.97). The model including all muscle and bone parameters provided the highest AUC (FNF: AUC 0.912; ITF: AUC 0.958), and AUC results of another selected model without muscle density showed that association with fracture significantly dropped (FNF: AUC 0.755; ITF: AUC 0.858). Separate results for the two age groups younger and older than 70 years showed no age‐related significant differences in discriminate models. Conclusions: Muscle density performs better than aBMD from hip computed tomography X‐ray absorptiometry and muscle size in discrimination of hip fracture. Combination of aBMD and muscle density provided the best discrimination. The integration of muscle assessments may trigger a paradigm shift in hip fracture prediction. Gluteus muscle density should also be evaluated as treatment outcome.